Do Bilinguals Have an Advantage in Theory of Mind? A Meta-Analysis - Schroeder, Scott R. (Frontiers in Communication, 2018)
Bilingualism might help children develop Theory of Mind, but the evidence is mixed. To address the disagreement in the literature, a meta-analysis was conducted on studies that compared bilingual and monolingual children on false belief and other Theory of Mind tests. The meta-analysis of 16 studies and 1,283 children revealed a small bilingual advantage (Cohen’s d=.22, p=.050). A secondary analysis was conducted on studies (k=8) that statistically adjusted the Theory of Mind scores to correct for a bilingual disadvantage in language proficiency. This secondary analysis indicated a medium-size bilingual advantage (Cohen’s d=.58, p<.001). There was no evidence for publication bias in either analysis. Taken together, the results provide support for a beneficial effect of acquiring two languages on mental state reasoning. Explanations for this bilingual advantage, which include bilingual-monolingual differences in executive functioning, metalinguistic awareness, and socio-pragmatic abilities, are discussed.